State ocean jurisdiction - Vrancken, P. H. G. (Routledge research in the law of the sea series, 2023)
"Proposing a systematic analytical framework which assists in understanding and applying the international law regime governing State ocean jurisdiction with a view to improved ocean governance for sustainable development, this book distinguishes between, and focuses on, the form, the ground, the scope and the purpose of State ocean jurisdiction"--